2021
DOI: 10.20944/preprints202104.0364.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Food Security, Environmental Health, and the Economy in Mexico: Lessons Learned with the COVID-19

Abstract: In Mexico, it is estimated that due to the economic system the overexploitation of natural resources, environmental impacts and health have been generated, with high rates of overweight and obesity. This review analyzes the impacts on food safety, environmental health, and the economy in Mexico before and during the COVID-19 contingency. Derived from the analysis, among the lessons learned we can include: the health contingency due to COVID-19 had negative repercussions on food security, environmental health a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…Anghinoni et al (2021), found that sustainability of agricultural production is critical to meet the growing demand for food, therefore, reducing environmental hazards is crucial to enhancing productivity. Similar findings were obtained by Monroy-Torres et al (2021), showing that the rumen microbiome is also responsible for the production of one of the most potent greenhouse gases. It is recommended that conventional methods to lower methane production by ruminants have proved successful but to a limited and often temporary extent.…”
Section: Econometric Resultssupporting
confidence: 83%
“…Anghinoni et al (2021), found that sustainability of agricultural production is critical to meet the growing demand for food, therefore, reducing environmental hazards is crucial to enhancing productivity. Similar findings were obtained by Monroy-Torres et al (2021), showing that the rumen microbiome is also responsible for the production of one of the most potent greenhouse gases. It is recommended that conventional methods to lower methane production by ruminants have proved successful but to a limited and often temporary extent.…”
Section: Econometric Resultssupporting
confidence: 83%
“…On the one hand, Covid-19 has led to millions of people losing their lives, as well as causing potential long-term illness to those who get in contact with the disease (Akkaya et al, 2021;Enghard et al, 2021;Huang et al, 2021). On the other hand, large-scale lockdown and severe travel restrictions adopted all over the world have caused massive damage to the economy and society (Monroy-Torres et al, 2021), in the quality of living, people's mental health (Xiang et al, 2020;Kang et al, 2020;Al-Rahamneh et al, 2021) and even the rise of crime cases (Barasa et al, 2021), etc. To address these problems, a number of countries have set to return to the normal economic and social activities with a high proportion of the population received vaccination.…”
Section: Introductionmentioning
confidence: 99%
“…, 2021). On the other hand, large-scale lockdown and severe travel restrictions adopted all over the world have caused massive damage to the economy and society (Monroy-Torres et al. , 2021), in the quality of living, people's mental health (Xiang et al.…”
Section: Introductionmentioning
confidence: 99%